2008
DOI: 10.1111/j.1863-2378.2008.01146.x
|View full text |Cite
|
Sign up to set email alerts
|

Serological Evidence of USUTU Virus Occurrence in North‐Eastern Italy

Abstract: In the recent years, USUTU virus (USUV), a flavivirus of the Japanese encephalitis virus complex, has been reported in Central Europe. As part of a systematic surveillance programme to monitor possible entrance and/or circulation of vector-borne viruses, since 2001, sentinel-chicken flocks were placed throughout the Italian territory nearby areas considered at risk of virus introduction. They have been periodically checked for the presence of antibodies against flaviviruses by indirect ELISA, plaque reduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
47
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 33 publications
4
47
0
Order By: Relevance
“…Lelli et al, 2008;Manarolla et al, 2010;Tamba et al, 2011; Vázquez et al, 2011;Cerutti et al, 2012;Ravanini et al, 2012;Buchebner et al, 2013;Calzolari et al, 2013a; Höfle et al, 2013). In Europe, USUV has been recognized as a candidate human pathogen in Austria (Weissenböck et al, 2007), Italy (Cavrini et al, 2009;Pecorari et al, 2009;Savini et al, 2011;Gaibani et al, 2012Gaibani et al, , 2013Pierro et al, 2013) and Croatia (Vilibic-Cavlek et al, 2014), but the pathogenicity for humans still requires further assessment.…”
Section: Introductionmentioning
confidence: 99%
“…Lelli et al, 2008;Manarolla et al, 2010;Tamba et al, 2011; Vázquez et al, 2011;Cerutti et al, 2012;Ravanini et al, 2012;Buchebner et al, 2013;Calzolari et al, 2013a; Höfle et al, 2013). In Europe, USUV has been recognized as a candidate human pathogen in Austria (Weissenböck et al, 2007), Italy (Cavrini et al, 2009;Pecorari et al, 2009;Savini et al, 2011;Gaibani et al, 2012Gaibani et al, , 2013Pierro et al, 2013) and Croatia (Vilibic-Cavlek et al, 2014), but the pathogenicity for humans still requires further assessment.…”
Section: Introductionmentioning
confidence: 99%
“…64 However, further studies conducted in the UK did not confirm USUV circulation in the country. 65,66 Seroconversion was also observed in Italy in the summer of 2005 67 and in 2007-2008, 68 although no virus could be rescued from these animals, and in France in 2009-2010, even though cross-reactivity with WNV could not be discarded. 71 Although the drop in screened positive birds in the region during the course of the sampled years may be due to herd immunity acquired in previous seasons, the study showed that the virus spread from the original area of emergence to surrounding areas of the country.…”
Section: µMmentioning
confidence: 96%
“…In northern Italy, antibodies against USUV were found in sera of sentinel chickens from 2005 and 2007 [45,46]. Also in Italy, sera of horses in the Tuscany region and North-East Italy collected in 2008 and 2009 were positive for USUV-specific antibodies [47].…”
Section: Current Knowledge About the Pathogenmentioning
confidence: 99%